2017
DOI: 10.1093/abbs/gmx002
|View full text |Cite
|
Sign up to set email alerts
|

Rce1 expression in renal cell carcinoma and its regulatory effect on 786-O cell apoptosis through endoplasmic reticulum stress

Abstract: Ras and a-factor-converting enzyme 1 (Rce1) is located in the endoplasmic reticulum (ER) and is thought to be responsible for endoproteolytic processing of the vast majority of CAAX proteins. Endoplasmic reticulum stress (ERS) plays an important role in renal cell carcinoma (RCC); however, the expression and role of Rce1 in RCC have not been extensively studied. We aimed to investigate the expression of Rce1 in RCC tissues and its molecular mechanism in ERS-induced apoptosis in RCC 786-O cells. We first used w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Several studies related to ccRCC reported that ER stress contributes to the alleviation of cancer malignant phenotypes. Downregulation of Rce1 enables RCC cell apoptosis by driving the PERK signaling pathway ( Li et al, 2017 ). The silencing of the expression of MSRB3 enhanced the expression of ER stress-related genes and inhibited the proliferation, migration, and invasion of ccRCC cells ( Ye et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies related to ccRCC reported that ER stress contributes to the alleviation of cancer malignant phenotypes. Downregulation of Rce1 enables RCC cell apoptosis by driving the PERK signaling pathway ( Li et al, 2017 ). The silencing of the expression of MSRB3 enhanced the expression of ER stress-related genes and inhibited the proliferation, migration, and invasion of ccRCC cells ( Ye et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rce1 is a novel type II CAAX isoprenyl endopeptidase that can hydrolyze three amino acids from Ras to participate in posttranslational modifications that facilitates its relocalization to the plasma membrane (Hampton et al, ; Manolaridis et al, ). There is increasing evidence that Rce1 plays a crucial role in the development of multiple malignancies (Huang et al, ; Jaworski et al, ; J. Li et al, ). Based on a previous study of EMT in HCC, we collected 131 cases of HCC and matched paratumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Rce1 participates in posttranslational modification of Ras in the endoplasmic reticulum and undergoes subsequent methylation and additional transcription processing (Jaworski et al, ; Stout & Campbell, ). Research works have shown that Rce1 plays a crucial role in the cancerogenesis and development of various malignant tumors, such as renal cell carcinoma (J. Li et al, ), prostate cancer (Huang et al, ), and colorectal cancer (Shi et al, ). At present, Rce1 has not been studied in HCC and the specific molecular mechanism of Rce1 in the early invasion and metastasis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development and testing of RPIs and MTIs substantially lag that of prenyl transferase inhibitors. Rce1 is also being investigated as a potential biomarker in various types of cancer, but its utility as a disease predictor remains far from being understood ( Huang et al 2016 ; Li et al 2017 ; Shi et al 2017 ).…”
Section: Clinical Relevance Of Rce1mentioning
confidence: 99%